(untitled) (Aporia, 2019)
There are five overlapping ethical objections to the creation of chimera: 1) Unnaturalness; 2) Species Integrity; 3) Moral Taboo; 4) Environmental Risk and 5) Chimera Welfare. This chapter will briefly outline the first four, before arguing that considerations of chimera welfare provides us with a strong reason against the creation of some, but not all, chimera. According to the argument from unnaturalness it is simply not our place to intervene in the basic mechanisms of nature. Critics of this view often challenge the coherence of any distinction between nature and human convention and the implicit assumption that nature is perfect as it is . Furthermore, it is often argued that, ad absurdum, the argument leads us to condemn as immoral the damning of rivers and the ploughing of fields...